Validity and Application of Practice Directions in Judicial Administration from the Perspective of Shariah and Civil Law: A Comparison: (Keabsahan dan Pemakaian Arahan Amalan dalam Pentadbiran Kehakiman dari Perspektif Undang-Undang Syariah dan Sivil: Suatu Perbandingan) (Kanun: Jurnal Undang-undang Malaysia, 2021)
Practice Directions have been introduced in the civil courts since 1946, and an adaptation of these was introduced in the Syariah courts in 2000. This article aims to explain the validity and position of the Practice Directions, as well as to compare these in terms of of legal provisions and application in the Syariah and civil courts. This research is a qualitative study involving library research (analysis of provisions of relevant laws and case reports), supplemented with interviews. It is found that Practice Directions were applied based on the provisions of the laws in force. However, there are differences in the position and application of Practice Directions between the Syariah courts and the civil courts in terms of source of authority, the authorities issuing the Practice Directions, enforcement and status, as well as the publication of Practice Directions. This study may serve as a guideline for JKSM and JKSN to re-evaluate and amend existing laws, or to form methods for Practice Directions for the courts to ensure that the ones used are valid and cannot be challenged by any party.Keywords: Practice Directions, judicial administration, Syariah court, civil court, shariah law, civil law, practice direction methods